To study the association of Doppler derived indices of uterine artery resistance with composite of PIH/PET - Rana, Uday Bhanu; Minhas, Santosh; Negi, Prakash; Pathania, Kushla; Kaur, Simar Preet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders of pregnancy (HDP) are among the main public health issues worldwide. They account for an estimated 10-15% of maternal deaths globally. Among the hypertensive disorders of pregnancy, pre-eclampsia is most dangerous, occurring in 10% of first pregnancies, and in 20-25% of women with past history of hypertension. The objective of present study is to investigate the association of Doppler derived Indices of uterine artery resistance with composite of PIH/PET. Methods: A prospective follow up observational study, including pregnant women at 11-13+6 weeks of gestation in whom Uterine Artery Resistance measured using Doppler ultrasound. Results: A total of 100 subjects were enrolled, out of which 11 developed pre-eclampsia/ gestational hypertension. All Doppler indices (Resistance Index, Pulsatility Index and Systolic/Diastolic Index) had high specificities and negative predictive values. Conclusions: The potential advantages of early screening of hypertensive disorders and their associated complications may allow investigations or prophylactic interventions before 20 weeks of gestation.